Antibacterial activity and heavy metal removal efficiency of electrospun medium molecular weight chitosan/nylon-6 nanofibre membranes. (7th December 2017) - Jabur, Akram R
Abstract: Chitosan/nylon-6 nanofibres with antibacterial activity properties were prepared by electrospinning a chitosan/nylon-6 solution (containing medium molecular weight chitosan). Nanofibres with diameters in the range of 139–190 nm were obtained. The yield of low concentration chitosan/nylon-6 nanofibres was higher than that of high concentration chitosan/nylon-6 nanofibres. The affinity of chitosan toward lead was studied using a Pb(NO3 )2 solution containing Pb(II) ions as the heavy metal solution. The rejection of lead ions by the chitosan/nylon membranes was investigated under various chitosan concentrations. The optimum removal values for Pb(NO2 )3 and NaCl were found to be 74% and 71%, respectively. The nanofibres developed in this study exhibited an excellent antibacterial activity (95%) against Escherichia coli .